Outcomes following PCI in CABG candidates during the COVID‐19 pandemic: The prospective multicentre UK‐ReVasc registry. Issue 2 (4th May 2021) - Kite, Thomas A.; Ladwiniec, Andrew; Owens, Colum G.; Chase, Alexander; Shaukat, Aadil; Mozid, Abdul M.; O'Kane, Peter; Routledge, Helen; Perera, Divaka; Jain, Ajay K.; Palmer, Nick; Hoole, Stephen P.; et al.
Abstract: Objectives: To describe outcomes following percutaneous coronary intervention (PCI) in patients who would usually have undergone coronary artery bypass grafting (CABG). Background: In the United Kingdom, cardiac surgery for coronary artery disease (CAD) was dramatically reduced during the first wave of the COVID‐19 pandemic. Many patients with "surgical disease" instead underwent PCI. Methods: Between 1 March 2020 and 31 July 2020, 215 patients with recognized "surgical" CAD who underwent PCI were enrolled in the prospective UK‐ReVasc Registry (ReVR). 30‐day major cardiovascular event outcomes were collected. Findings in ReVR patients were directly compared to reference PCI and isolated CABG pre‐COVID‐19 data from British Cardiovascular Intervention Society (BCIS) and National Cardiac Audit Programme (NCAP) databases. Results: ReVR patients had higher incidence of diabetes (34.4% vs 26.4%, P = .008), multi‐vessel disease with left main stem disease (51.4% vs 3.0%, P < .001) and left anterior descending artery involvement (94.8% vs 67.2%, P < .001) compared to BCIS data. SYNTAX Score in ReVR was high (mean 28.0). Increased use of transradial access (93.3% vs 88.6%, P = .03), intracoronary imaging (43.6% vs 14.4%, P < .001) and calcium modification (23.6% vs 3.5%, P < .001) was observed. No difference in in‐hospital mortality was demonstrated compared to PCI and CABG data (ReVR 1.4% vs BCIS 0.7%, P = .19; vs NCAP 1.0%, P = .48). Inpatient stay was half compared to CABG (3.0 vs 6.0 days). Low‐event rates in ReVR were maintained to 30‐day follow‐up. Conclusions: PCI undertaken using contemporary techniques produces excellent short‐term results in patients who would be otherwise CABG candidates. Longer‐term follow‐up is essential to determine whether these outcomes are maintained over time.